Concurrent Intratonsillar, Peritonsillar, and Retropharyngeal Abscesses: Case Report of Multiple Deep Neck Space Infection - Yovita Hamdani; Henny Widyastuti (CV. Publikasi Indonesia, 2026)
Deep neck space infections are potentially life-threatening conditions due to their proximity to vital structures such as the airway, major blood vessels, and cranial nerves. These infections may spread rapidly and lead to severe complications, including airway obstruction and sepsis. This study aims to describe a rare case of concurrent intratonsillar, peritonsillar, and retropharyngeal abscesses, as well as to evaluate the effectiveness of conservative management using intravenous antibiotics. This research employed a descriptive qualitative case report approach involving a 32-year-old male patient presenting with progressive throat pain, dysphagia, neck swelling, and a muffled voice. Data were collected through clinical examination, laboratory tests, and radiological imaging, followed by continuous observation during hospitalization. The findings revealed elevated leukocyte levels and radiographic evidence of retropharyngeal space widening. The patient was treated with intravenous cefotaxime and metronidazole, along with supportive therapy. Significant clinical improvement was observed within 48 hours, with resolution of symptoms by the fifth day without surgical intervention. In conclusion, early diagnosis and prompt antibiotic therapy can effectively manage selected cases of multiple deep neck abscesses. Conservative treatment may be considered in stable patients, potentially avoiding invasive procedures while ensuring favorable clinical outcomes